Hydrophobic core/shell particles via miniemulsion polymerization - Etmimi, Hussein Mohamed (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.